The implementation of Geographical Information System for Monitoring the Population in Cimahi - Hamdani, Dani; Indra Sentana, Kadek; Sulistiono, Mellivia; Martha Rischi, Vellya; Andriana, Yandhi (International Journal of Psychosocial Rehabilitation, 2020)
All development planning at the local and national levels requires basic population information such as population, age, sex, and other characteristics. This study discusses the implementation of Geographic Information Systems to monitor the population in Cimahi. QGIS was chosen because it has a programming language that can allow various types of spatial data to be open from any source. The final results of the geographic information system that has been made can display information about the distribution of the population visually. In addition, this geographic information system can also provide information about regional population density data.